Comparative analyses of thermodynamic properties assessments, performed by geometric models: Application to the Ni-Bi-Zn system - Gandova V.; Vassilev G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The thermochemical properties of metals and alloys are essential for the chemists to invent and improve metallurgical and materials’ design processes. However, the properties of multicomponent systems are still scarcely known due to experimental difficulties and the large number of related systems. Thus, the modelling of some thermodynamic properties would be advantageous when experimental data are missing. Considering mentioned facts, geometric models to estimate some thermodynamic properties for the liquid phase of the Ni-Bi-Zn systems. The calculations have been performed in a wide temperature range (1000-2000 K). Ternary interaction parameters for the liquid phase allowing molar Gibbs excess energy calculation have been determined.